2013
DOI: 10.1038/nature12068
|View full text |Cite
|
Sign up to set email alerts
|

Future sea-level rise from Greenland’s main outlet glaciers in a warming climate

Abstract: Over the past decade, ice loss from the Greenland Ice Sheet increased as a result of both increased surface melting and ice discharge to the ocean 1,2 . The latter is controlled by acceleration of ice flow and subsequent thinning of fast-flowing marine-terminating outlet glaciers 3 . Quantifying the future dynamic contribution of such glaciers to sea-level rise (SLR) remains a major challenge since outlet-glacier dynamics are poorly understood 4 . Here we present a model that includes a fully dynamic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
302
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(321 citation statements)
references
References 28 publications
17
302
2
Order By: Relevance
“…Csatho et al [67] found that mass loss is not proportional to the drainage basin area, and that the majority of Greenland mass loss during the 2003-2009 period (∼80 %) was due to thinning of small to moderately sized drainage basins rather than the four large glaciers modeled by Nick et al [95]. In contrast, Enderlin et al [69] found that these four glaciers represented 42 % of the ice sheet discharge change from 2000 to 2012 as opposed to the 20 % expected from an assumption of proportionality with drainage area.…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…Csatho et al [67] found that mass loss is not proportional to the drainage basin area, and that the majority of Greenland mass loss during the 2003-2009 period (∼80 %) was due to thinning of small to moderately sized drainage basins rather than the four large glaciers modeled by Nick et al [95]. In contrast, Enderlin et al [69] found that these four glaciers represented 42 % of the ice sheet discharge change from 2000 to 2012 as opposed to the 20 % expected from an assumption of proportionality with drainage area.…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
“…Projections of SMB were made based on a relation between mass loss and temperature derived from regional climate modeling forced with CMIP5 AOGCMs [94], with additional allowances for methodological uncertainties and changes in ice sheet topography [88]. Projections of rapid change in discharge were based largely on flowline modeling of four of the larger outlet glaciers, with results scaled up by ∼5 times because these glaciers drain ∼20 % of the ice sheet by area [95], giving likely ranges of 0.02 to 0.09 m by 2100 for RCP8.5, and 0.01 to 0.06 m for the three RCPs of lower forcing, for which there was insufficient information to assess scenario dependence [88]. Likely ranges for projections of the total contributions to GMSL rise by 2100 relative to 1986-2005 range from 0.04 to 0.12 m for RCP2.6 to 0.09 to 0.28 m for RCP8.5 [88].…”
Section: Greenland Ice Sheetmentioning
confidence: 99%
“…The computation of the crevasse penetration depth is based on the work of Nye (1957), and depends on the equilibrium between longitudinal stretching (opening term) and cryostatic pressure (closing term). This so-called "crevasse depth" criterion has been applied to individual marine-terminated glaciers in Greenland and Antarctica, and enabled the successful reproduction of variations in the front (Nick et al, 2010;Otero et al, 2010;Nick et al, 2013;Cook et al, 2014). Although the model of Nick et al (2010) accounts for basal crevasse propagation, which improves the ability of a model to reproduce observed behaviour, it is based on an instantaneous stress balance combined with an empirical criterion for calving.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating the effects of ponded meltwater (allowing deeper crevasse penetration) also allows calving rates to be driven by climate fluctuations via changes in surface runoff (e.g. Nick et al, 2013). These physically-based calving mechanisms have begun to be implemented in numerical modelling (e.g., of Antarctica) (Albrecht et al, 2011;Levermann et al, 2012;Pollard and DeConto, 2012;Albrecht and Levermann, 2014;Pollard et al, 2015), but remain particularly challenging in palaeo-applications where the intermittent and often rapid nature of the calving process has to be properly accounted for on long timescales.…”
mentioning
confidence: 99%